Bahasa Inggris - Nugraha, Hasan Adi; Samsul Ma’arip; Naufal Athiyya Hammam; Nazwa Nurannisa P S; Riski Firnanda; Muhammad Aulia Rahman (LPPM Politeknik Aceh Selatan, 2025)
This study optimizes propellerless wind power generation using a multidimensional approach and IoT technology. CFD simulations identified the S1210 airfoil as optimal due to its efficiency at low Reynolds numbers. The simulations revealed that a 9-degree angle of attack produced higher velocity and lower pressure, enhancing airflow and theoretical power output. Further simulations varying the distance between mirrored airfoils showed that an optimal distance exists for different wind speeds. An IoT system was then implemented to adjust this distance dynamically. Through in-depth analysis of airfoil design, material selection, and the application of IoT technology, this research pioneers a way to improve wind farm efficiency, overcome efficiency challenges at low wind speeds, and reduce maintenance costs. Its contribution is not only limited to the development of cleaner renewable energy technologies, but also opens the door to a deeper understanding of wind energy dynamics and its utilization on a large scale.